Politics and Efficiency of Separating Capital and Ordinary Government Budgets* - Bassetto, Marco; Sargent, Thomas J (Quarterly Journal of Economics, 2006)
We analyze the democratic politics of a rule that separates capital and ordinary account budgets and allows the government to issue debt only to finance capital items. Many national governments followed this rule in the 18th and 19th centuries and most US states do so today. Despite its simplicity, this 1800s financing rule provides excellent incentives for majorities to choose an efficient mix of public goods in an economy with a growing population of overlapping generations of long-lived but mortal agents. In a special limiting case of our model where the demographics make Ricardian equivalence prevail, the 1800s rule does nothing to promote efficiency. But when the demographics imply even a moderate departure from Ricardian equivalence, imposing the rule substantially improves the efficiency of democratically chosen allocations. We calibrate some examples to U.S. demographic data and use our findings to offer a tentative explanation for why the 1800s rule was abandoned by the Federal government but not by state governments in the twentieth century